Uushiindaism as a collective poverty alleviation mechanism and social support (JULACE: Journal of the University of Namibia Language Centre, 2018)
There are attempts to break the cycle of poverty among indigent people in communities globally and in Namibia in particular. In Africa, attempts are made to devise various strategies and develop tools to alleviate poverty. There is, thus a need to implement poverty alleviation tools based on the indigenous knowledge system. By employing and promoting the existing tools among the indigenous people, poverty is likely to be alleviated. This paper presents uushiindaism as one of the existing indigenous tools that can be used to lessen poverty among the poor and marginalized people. Using the collectivism theory which advocates for communal, societal, or national interests in various types of political, economic, and educational systems, the study investigates the concept of uushiindaism as practiced by Aawambo. Data was collected through semistructured interviews. The narrative approach is used in the paper to unravel the role, significance and relevance of uushiindaism and to highlight threats to uushiindaism. It is revealed, in this paper, that poverty may be alleviated through sharing of resources, coupled with work related programs and not through the creation of dependency syndrome.
Keywords: uushiindaism; poverty alleviation mechanism; social support; marginalized people; collectivism theory; Aawambo